2018
DOI: 10.1177/0361198118794055
|View full text |Cite
|
Sign up to set email alerts
|

Roadway-Related Truck Crash Risk Analysis: Case Studies in Texas

Abstract: Since 1994, Texas has had the highest number of fatal crashes involving large trucks in the United States, and this number increased by 82% from 2009 to 2012. Due to the size and weight of large trucks, their crashes usually are very destructive. Although large trucks have a significant impact on traffic safety in Texas, very little analysis has been conducted of the risk factors associated with crashes involving large trucks, especially the roadway-related risk factors. In this paper, the results of a collisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Since 1994, Texas has had the highest number of fatal crashes involving large trucks in the U.S. [ 1 ].Among these large truck crashes, the AK level crashes (A is the incapacitating crash, and K is the fatal crash) often result in immense social and economic losses. To prevent and mitigate the occurrence of AK level truck crashes, factors that significantly contribute to such severe crashes need to be identified before appropriate countermeasures can be explored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 1994, Texas has had the highest number of fatal crashes involving large trucks in the U.S. [ 1 ].Among these large truck crashes, the AK level crashes (A is the incapacitating crash, and K is the fatal crash) often result in immense social and economic losses. To prevent and mitigate the occurrence of AK level truck crashes, factors that significantly contribute to such severe crashes need to be identified before appropriate countermeasures can be explored.…”
Section: Introductionmentioning
confidence: 99%
“…*1 The significance level of the estimated correlation coefficient, *2 MDI denotes Mean Decrease Impurity. * 3 ML denotes Machine Learning.…”
mentioning
confidence: 99%
“…Another study analyzing the injury severity associated with work zones found that daytime crashes, higher speed limits, no traffic control during access, and crashes on rural principal arterials substantially increased the likelihood of severe crashes [20]. Traffic engineers and roadway designers should adopt better, safer, and more efficient geometric designs and traffic control strategies, as roadway-related variables are more controllable, to assist with reducing specific types of crashes [21].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Apart from the common modeling techniques, other statistical and innovative machine learning methods have been used to examine the injury severity and crash frequency of large truck-related crashes. Some of these examples consist of the classification tree model ( 19 ), hierarchical Bayesian random intercept model ( 20 ), skewed logistic model ( 21 ), and a risk analysis model dependent on collision diagram ( 22 ). Even though most of these studies concentrated on highway crashes, Qin et al analyzed the factors contributing to the severity and frequency of truck-related crashes at freeway diverging section with the use of NB and MNL models ( 23 ).…”
Section: Literature Reviewmentioning
confidence: 99%